A healthful home food environment: Is it possible amidst household chaos and parental stress?. (1st November 2019) - Fulkerson, Jayne A.; Telke, Susan; Larson, Nicole; Berge, Jerica; Sherwood, Nancy E.; Neumark-Sztainer, Dianne
Abstract: Purpose: This study examines how household chaos and unmanaged parental stress are associated with and contribute to variance in markers of the home food environment (family meal frequency, perceived barriers to cooking, healthful home food availability). Obtaining a better understanding of these relationships could guide more effective family-based interventions to promote healthful home food environments. Methods: The analytic sample included 819 households with children in the population-based Project EAT-IV cohort with survey data from 2015 to 2016. Multiple linear regression was used to generate means and 95% confidence intervals of home food environment variables, and estimates for the contribution of household chaos (defined by frenetic activity, loud noises and disorder), and quartiles of unmanaged parental stress (ratio of perceived stress and ability to manage stress). Model fit was also examined. Results/findings: Both household chaos and quartiles of unmanaged parental stress were independently and inversely associated with family meal frequency (p's < 0.001) and positively associated with perceived mealtime preparation barriers (p's < 0.001). Unmanaged parental stress was also inversely associated with healthful home food availability (p = 0.004). Models including demographic characteristics, household chaos scores, and quartiles of unmanaged parental stress index showed significantly improved model fit for all outcomes compared to less comprehensive models. Among families with high chaos, those having 7 + family meals/week were significantly more likely to have lower mealtime preparation barrier scores, younger children and higher healthful home food availability scores than families eating together less often. Conclusions: Interventions to assist with parental management of stress and chaos within the home environment (e.g., establishing routines) may increase family meal frequency and the quality of children's home food environments.